1997
DOI: 10.1258/0956462971918887
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant human interferon- in the treatment of condylomata acuminata

Abstract: The number of clinic consultations for condylomata acuminata (genital warts) has increased substantially during the last 30 years. Most infections produce benign lesions but a few types may be associated with cervical and penile cancers. Interferons (IFN) have shown antiviral properties to these infections and IFN-beta in particular has demonstrated a specific cytopathic effect in humans. A total of 124 patients with condylomata acuminata, the majority of whom had failed previous therapy, were treated intrales… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…21,22 Although IFN-␣ and IFN-␤ have been considered to share many of their biological activities, mainly because of the binding to the same receptor, evidence exists indicating possible differences in their in vitro and in vivo effects, in terms of antiproliferative, [23][24][25][26][27][28][29] antiviral, 30,31 signal transduction, [32][33][34][35] immunomodulatory, 36 -39 anti-invasive, 40,41 and anti-angiogenic properties. 42,43 Although IFN-␤ as a single agent has been successfully used in the therapy of chronic hepatitis C, 44 some benign proliferative diseases, 45 and most recently in relapsing multiple sclerosis, 46 IFN-␣ is the most widely used cytokine in the therapy of certain human malignancies, 21 and its antitumor activity is generally assumed to be superior to that of IFN-␤, even though comparative clinical evaluations in cancer patients have not been performed.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Although IFN-␣ and IFN-␤ have been considered to share many of their biological activities, mainly because of the binding to the same receptor, evidence exists indicating possible differences in their in vitro and in vivo effects, in terms of antiproliferative, [23][24][25][26][27][28][29] antiviral, 30,31 signal transduction, [32][33][34][35] immunomodulatory, 36 -39 anti-invasive, 40,41 and anti-angiogenic properties. 42,43 Although IFN-␤ as a single agent has been successfully used in the therapy of chronic hepatitis C, 44 some benign proliferative diseases, 45 and most recently in relapsing multiple sclerosis, 46 IFN-␣ is the most widely used cytokine in the therapy of certain human malignancies, 21 and its antitumor activity is generally assumed to be superior to that of IFN-␤, even though comparative clinical evaluations in cancer patients have not been performed.…”
Section: Discussionmentioning
confidence: 99%
“…Cervical cancer: High-risk HPV subtypes (HPV 16 and HPV 18) are the causes of approximately 70% of invasive cervical cancer and it is estimated that 500,000 cases of cervical cancer occur each year worldwide. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] A study of paraffin-embedded samples of 10,575 cases of cervical cancer demonstrated that the most common HPV types were 16,18,31,33,35,45,52, and 58; HPV types 16 and 18 represented 71% of the cases overall. 25 Other anogenital cancers: Vaginal, vulvar, penile and anal cancers and their precancerous precursors such as vulvar intraepithelial neoplasia (IN), penile IN, anal IN are other associated neoplasies.…”
Section: Neoplasiamentioning
confidence: 99%
“…Experience with these agents is more limited than for other medical therapies. [49][50][51][52][53] Imiquimod: Imiquimod is a toll-like receptor 7 agonist, which acts as a positive immune response modifier, and stimulates local cytokine induction. Two formulations are available, Aldara (5% imiquimod) and Zyclara (3.75% imiquimod).…”
Section: Immune-mediated Therapiesmentioning
confidence: 99%
“…Complete response rates for IFN treatment groups generally varied from 28% 191 to 100% 195 with 9 out of 16 studies surveyed reporting complete response rates between 40% and 60%. 186,188,190,192,193,[196][197][198][199] Furthermore, warts treated with intralesional IFN may continue to resolve for days to weeks after the treatment. 187 While most intralesional IFN studies focus on IFNa treatments, IFNf3 has been studied and demonstrated results comparable to IFNa in most trials.…”
Section: Interferonsmentioning
confidence: 99%
“…187 While most intralesional IFN studies focus on IFNa treatments, IFNf3 has been studied and demonstrated results comparable to IFNa in most trials. [194][195][196][197][198][199] Systemic IFN therapy of genital warts has been studied with IFNa, IFNf3, and IFN')'.200-216 These studies reported highly variable results. IFNa demonstrated complete response rates in IFN treatment groups ranging from 18%209 to 71%207 with 6 out of9 studies (with more than 2 participants) reporting complete response rates between 20% and 50%.…”
Section: Interferonsmentioning
confidence: 99%